The Engineer as a Teacher: Professional Teaching Identity of Engineers in Spain - Carrasco-Aguilar, Claudia; Ortiz-Mallegas , Sebastián; Martín-Civantos, Mariano; Luzón Trujillo, Antonio (International Journal of Engineering Pedagogy (iJEP), 2025)
The professional teaching identity of engineers who teach has been scarcely studied. This study employed a narrative approach to analyze the teaching identity of 17 engineers across three groups: those who train future engineers, those who prepare future science, technology, engineering, and mathematics (STEM) teachers, and those who are training to become STEM educators. Three dimensions of teaching identity were examined: personal, professional, and situational. Findings indicate that university professors construct their identity based on their personal trajectories, whereas future STEM educators emphasize their individual characteristics as key to their performance. Additionally, engineers who teach recognize the need for specific pedagogical training, yet they often rely on peer learning due to limited institutional support. Moreover, among those training to become teachers, professional experience in engineering is valued more highly than teaching practice. These results highlight the significance of context, career trajectory, and institutional support in shaping the teaching identity of engineers.